2017
DOI: 10.1371/journal.pone.0171555
|View full text |Cite
|
Sign up to set email alerts
|

Collective behavior quantification on human odor effects against female Aedes aegypti mosquitoes—Open source development

Abstract: Classifying and quantifying mosquito activity includes a plethora of categories, ranging from measuring flight speeds, repellency, feeding rates, and specific behaviors such as home entry, swooping and resting, among others. Entomologists have been progressing more toward using machine vision for efficiency for this endeavor. Digital methods have been used to study the behavior of insects in labs, for instance via three-dimensional tracking with specialized cameras to observe the reaction of mosquitoes towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, in this study, a more specific design is required as shown in Fig 1, which is a modified version from a previous closely related research [20]. …”
Section: Methodsmentioning
confidence: 99%
“…However, in this study, a more specific design is required as shown in Fig 1, which is a modified version from a previous closely related research [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Overall, the technical development has led to a variety of tracking systems to choose from, a reduction in costs and an increase in the portability of recording set-ups. Advantages and disadvantages of quantification techniques have recently been summarized in a non-exhaustive list by Poh et al [ 153 ]. It is remarkable that the table lists a variety of techniques that are described as either ‘complex to set up’ or ‘cover a small area of observation’ indicating that there is still much room for improvement.…”
Section: Insect Flight Tracking: the State Of The Artmentioning
confidence: 99%
“…This paper 26 describes one such model: a fine-grained agent-based approach for modelling how indoor 27 insecticide treatments deployed as residues on bed nets affect the behavior and survival 28 of mosquitoes. 29 To capture the complex interactions between mosquitoes and a human host lying 30 beneath an insecticide-treated bed net, individual mosquito flight paths and local 31 interactions within the indoor environment are required. Yet most modelling approaches 32 to disease transmission by insect vectors set the scale at a much higher level, 33 emphasizing interactions at village scale (and above) [11], [12].…”
mentioning
confidence: 99%
“…Recent technological developments in imaging and computing have enabled accurate 73 tracking of mosquito flight dynamics. This is achieved by analyzing video recordings of 74 mosquitoes and applying image processing and analysis methods to reconstruct and log 75 the flight paths and range from relatively simple approaches using a single 76 camera [30], [31] to more complex multi-camera methods [9], and 3D reconstruction 77 approaches [32], [33]. These multi-camera approaches allow the tracking of mosquito 78 flight around a bed net and therefore a more complex representation of bed net 79 occupancy at a 'life-size scale.…”
mentioning
confidence: 99%